Reflections of adolescent motherhood on infant and young child feeding practices: the case of Uganda - Gözde Zeynep Yeşiloğlu; Suzan Yalçin; Sıddika Songül Yalçin (BMC Public Health)
Abstract Background Age-appropriate breastfeeding and adequate complementary feeding play a crucial role in reducing under-5 mortality rates, malnutrition, and mortality worldwide. Given the high prevalence of adolescent pregnancy in Uganda, we aimed to assess the competence of adolescent mothers in infant and young child feeding (IYCF) using data from the 2016 Uganda Demographic Health Survey. Method Our sample comprised the last children aged 6–23 months of mothers aged 15–29 years, totaling 2594 mother-infant pairs; 402 were aged 15–19 years, 1,388 were aged 20–29 years with their first delivery before the age of 20, and 804 were aged 20–29 years with their first delivery at 20 years or older. We utilized complex sample logistic regression analysis to examine the interactions between adolescent motherhood and IYCF indicators during the previous day of the survey. Results The rates of ongoing breastfeeding, bottle feeding, minimum meal frequency, minimum dietary diversity, minimum acceptable diet, egg and/or flesh food consumption, zero vegetable or fruit consumption, and unhealthy food consumption were found to be 77.7%, 16.3%, 37.5%, 28.7%, 14.2%, 41.7%, 31.6%, and 14.7%, respectively. Multivariate complex sample logistic regression revealed that women with a history of adolescent pregnancy had lower odds of achieving minimum meal frequency, and higher odds of zero vegetable or fruit consumption. Conclusion Adolescent mothers and women who give birth during their teenage years are particularly vulnerable to inadequate infant and young child nutrition practices. Targeted interventions and education programs should be implemented to promote optimal complementary feeding practices among mothers in Uganda.